Pengaruh Penggunaan Cairan Pendingin (Coolant) terhadap Keausan Pahat Bubut HSS - Widiyawati, Sri; Novareza, Oyong; Sulistyarini, Dwi Hadi; Putro, Wisnu Wijayanto (Jurnal Rekayasa Mesin, 2020)
Lathe Machine can use for several kinds of the process such as turning, drilling, boring, tapering, and threading. The lathe machine process requires some interaction between processing material with the chisel. Time processing that reaches the worn-out limit is likely called chisel life. One of the factors that affected chisel worn-out is the use of coolant. Therefore researched the effect of one of the variable process that is coolant to HSS Carbide worn-out chisel to predict the lifetime of it. This research was conducted three times without using a coolant, using a coolant ratio of 1:30, and using a coolant ratio of 1:40. The spindle speed of the lathe used is 400 rpm. The tool wear was analyzed through measurement with callipers and the help of CorelDraw X7 software. Based on the measurements made, the results showed that the highest tool wear was found in HSS chisels with 1:40 coolant application, which was a reduction of 1.4 mm.